The student profile of selcuk university, faculty of veterinary medicine - Mehmet Emin Tekin (Eurasian Journal of Veterinary Sciences)
Aim: This study was carried out to reveal the success and partly demographic profile of students of Selcuk University, Faculty of Veterinary Medicine. Materials and Methods: In the study, the identifier information of students who were at the last year of education was used in 2008, 2009, 2010 and 2013 years (the data could not be collected at 2011 and 2012). Approximately 80% of students were introduced to the study and 433 data collected and revealed overall four years. The questions that asked to the students to identify were organized as a survey format and collected the data. The frequencies and rates of answers of each question were tabled and presented as graphics. Results: The gender of students were as 87.3% male and 12.7% female; the majority of students who entered this Faculty from regions of Central Anatolia (39.3%), Mediterranean (18.9%) and Aegean (13.6%); the 84.3% of students described their mother as housewife; the students whose father is worker were maximum (31.1%) and students whose father is officer were 28.1%; the majority of students had two (35.3%) and three (26.8%) siblings; the secondary education origin of students were high school (49.2%), Anatolian high school (29.8%) and super high school (16.5%); the majority (86.8%) of students stayed at students homes and very few (13.2%) of them at youth hostels; the rates of whom knowing a foreign language at a good level were only 21.8% and the others' knowing of language were weak or moderate; only 21.6% of the students who were interns had not a lesson at subclasses but the 46.4% of them had 1-3 lectures at subclasses; 66.6% of students had an average of lesson as under 2.5 point and only 5.9% of him had an average that upper 3.0 point. The 45.4% of students want to be an officer as the first preference. Conclusion: It is thought that this study has descriptive and directive for the Faculty managers, lecturers and students.